(untitled) - Lednicky, Martin; Slesinger, Jan; Sosedova, Jarmila (Doprava a spoje, 2010)
Through the Integrated Action Programmed for Inland Waterway Transport has recommended the EU to take concrete measures to fully exploit the market potential of inland navigation and its use more attractive. It is expected to introduce advanced educational programs learning tools operating on the basis of virtual reality and pay more attention to supporting the development of lifelong learning.